2012
DOI: 10.1128/jvi.06065-11
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Recombination Events in the Founding and Emergence of Subgenogroup Evolutionary Lineages of Human Enterovirus 71

Abstract: Enterovirus 71 (EV71) is responsible for frequent large-scale outbreaks of hand, foot, and mouth disease worldwide and represent a major etiological agent of severe, sometimes fatal neurological disease. EV71 variants have been classified into three genogroups (GgA, GgB, and GgC), and the latter two are further subdivided into subgenogroups B1 to B5 and C1 to C5. To investigate the dual roles of recombination and evolution in the epidemiology and transmission of EV71 worldwide, we performed a largescale geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
95
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 68 publications
(87 reference statements)
13
95
1
1
Order By: Relevance
“…This is comparable to those of other enteroviruses (enterovirus 71 [33], echovirus 6 [34][35][36][37], coxsackievirus A4 [38] and echovirus 3 [39]) but slightly higher than what was published for echovirus 9 and echovirus11 [23].…”
supporting
confidence: 76%
“…This is comparable to those of other enteroviruses (enterovirus 71 [33], echovirus 6 [34][35][36][37], coxsackievirus A4 [38] and echovirus 3 [39]) but slightly higher than what was published for echovirus 9 and echovirus11 [23].…”
supporting
confidence: 76%
“…Although recombination was evident in the 4 CVA2 strains, lack of comparative sequences indicated that the timing of recombination events was unknown, and low overall similarity to comparison sequences suggested that these events could be distant in time. As in many studies of human enterovirus A strains, lack of complete genome sequences for most serotypes, with the possible exception of EV71, limits interpretation of results for recombination analysis ( 10 , 11 ). In the present study, only 2 complete genome sequences of CVA4 strains (prototype strain High Point and strain SZ/CHN/09) were included in recombination analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Subgenogroup C4 has been found in the region since 1998 ( 8 ), and viruses from our study cluster with recent C4 viruses from the People’s Republic of China. Emergence of novel subgenotypes, often related to recombination events in noncoding regions ( 9 ), and switches of dominant subgenotypes are common and may be associated with large outbreaks. Most outbreaks reported in the Asia-Pacific region during the last decade were caused by previously undefined EV71 subgenogroups ( 10 ), but there is no evidence of differences in virulence.…”
Section: The Studymentioning
confidence: 99%